Construction of Indonesian cultural thoughts in tafsir al-Azhar as Hamka’s teaching practice; text analysis using George Herbert Mead communication theory - Hamdi Putra Ahmad (IAIN Salatiga, 2017)
Tafsir al-Azhar is one of the many exegesis books written by Nusantara scholars. Authored by Hamka, this book includes products come in the contemporary era and has attracted many researchers to analyze deeply all of the secrets contained in them. Tafsir al-Azhar contains a number of information related to the elements of Indonesia cultures. But not many of the readers are aware of this fact because of its relatively small capacity. It is the main attraction to be studied in depth in order to know how the construction built by a Hamka related to his Indonesian cultural thoughts contained in Tafsir al-Azhar. Using George Herbert Mead's social communication theory, this research will formulate the construction of the Indonesian cultural commentary constructed by Hamka in Tafsir al-Azhar and prove that the use of elements of Indonesian culture in interpreting the Qur'an is one of the effective strategies to teach about the Qur’anic interpretation to the Muslims in particular, and the Indonesian people in general.